Lay Ministers for Tomorrow's Church. - Brophy, Donald F. (America Magazine: The Jesuit Review of Faith & Culture, 1978)
The article focuses on the lay ministry which has become one of the hackneyed words in ecclesiastical jargon. It explores the evolution undergoing in ministries in which lay people are carrying out functions in the Christian community and apostolate that were reserved exclusively to the clergy several years ago. It shows the diversity of service in the Church with a unity in purpose, and the laity share their own role in the mission of the People of God in the Church and in the World.